2003
DOI: 10.1136/bmj.326.7399.1115
|View full text |Cite
|
Sign up to set email alerts
|

Stepping down inhaled corticosteroids in asthma: randomised controlled trial

Abstract: Objectives To determine whether the dose of inhaled corticosteroids can be stepped down in patients with chronic stable asthma while maintaining control. Design One year, randomised controlled, double blind, parallel group trial. Setting General practices throughout western and central Scotland. Participants 259 adult patients with asthma receiving regular treatment with inhaled corticosteroids at high dose (mean dose 1430 g beclomethasone dipropionate). Interventions Participants were allocated to receive eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 21 publications
3
79
0
4
Order By: Relevance
“…1) When inhaled glucocorticosteroids alone are being used in medium-to-high doses, a 50% reduction in dose should be attempted at 3-month intervals (Evidence B) [151,308,309].…”
Section: Stepping Down Treatment When Asthma Is Controlledmentioning
confidence: 99%
“…1) When inhaled glucocorticosteroids alone are being used in medium-to-high doses, a 50% reduction in dose should be attempted at 3-month intervals (Evidence B) [151,308,309].…”
Section: Stepping Down Treatment When Asthma Is Controlledmentioning
confidence: 99%
“…Nor could pulmonologists exclude the 'benefit of the doubt' when diagnosing asthma in patients using ICS who had a normal lung function and only minor complaints. For at least 30% of these patients, it was possible to decrease their dose of ICS without problems, which could indicate either achieved asthma control 17 or-in some patients-misdiagnosed 'asthma'. These facts suggest a higher number of patients using ICS unnecessarily and an underestimation of the problem we examined.…”
Section: Shortcomings Of This Studymentioning
confidence: 99%
“…Analysis of randomized controlled trial (RCT) studies that examined step-down of asthma medications suggested that each of the methods of stepping down from ICS to reduced ICS dose [58][59][60][61], scheduled ICS to on demand ICS [57,62], or ICS to leukotriene receptor antagonist (LTRA) [63] may be safe options for many patients with stable asthma. However, each of these step-down strategies likely confers an increased risk of having an exacerbation or loss of asthma control compared with continuing the current asthma regimen.…”
Section: Stepwise Dose Reduction Of Icsmentioning
confidence: 99%